Face Threatening-Acts In Indonesia Fourth Vice Presidential Candidate Election Debate (2024): Pragmatics Study - Syafira Hasya Putri Rezkian; Ervina CM Simatupang (Universitas Cokroaminoto Palopo, 2024)
The research investigates face-threatening acts (FTAs) in the fourth vice-presidential election debate in Indonesia, applying a pragmatic approach to analyze how strategies and acts used impact the candidates’ electability and credibility. This study also focused on the word choices during the debate that can be considered rude or put the other candidates in an uncomfortable situation and how this affects the flow of debate. Qualitative procedures including display data, quoting, and authentication were used in the data analysis process. By applying the politeness theory of Brown and Levinson, the study classifies and divides the FTAs into positive and negative faces. According to the study, the three candidates regularly use strategies meant to harm the public perceptions of their opponents in order to influence voter opinions and affect election results. The research offers insights into the purpose of communication tactics in political debates and their broader impact on political discourse and election outcomes by comprehending the dynamics of FTAs in this high-stakes environment.